A return to geopolitics? The future of the security community in the Baltic Sea Region - Ekengren, Magnus (Global affairs (Abingdon, Oxfordshire, UK), 2018)
One key question for the European security community is whether today's confrontation between the EU member states and Russia is the end of its spread to the Baltic Sea region, including Russian districts, and the beginning of a return of geopolitical rivalry in the region. This article investigates the possibilities of avoiding such a negative downward spiral by drawing on security community theory and discussing two different methods of security community building - "top-down" and "bottom-up". It points to the need for the EU institutions to return to the Monnet method to find a way out of the geopolitical "zero-sum" game increasingly played by the governments in the region. This implies not putting restrictions on participants from the north-west regions of Russia in strategically chosen areas of cooperation, and a more pronounced bottom-up, long-term and macro-regional approach built on joint problem-solving projects and people-to-people contacts that generate "win-win" games.